ANALISIS NILAI JUAL OBJEK PAJAK DAN IMPLIKASINYA TERHADAP PAJAK BUMI DAN BANGUNAN (PBB) DI KECAMATAN BETOAMBARI KOTA BAUBAU - Pardana, Deki (JISEF : Journal Of International Sharia Economics And Financial, 2022)
This research was conducted at the Baubau City Regional Finance, Asset and Revenue Agency, Southeast Sulawesi Province. The population in this study is the entire sale value of the tax object in Betoambari sub-district. The sample in this study were all villages in Betoambari sub-district, namely Sulaa village, Lipu village, Katobengke village, Labalawa village and Waborobo village. Data analysis in this study uses qualitative data analysis, where data is presented in the form of a Numeric scale (numbers) for example, data on the List of Determination of the Selling Value of Tax Objects (NJOP). Based on the results of research on the determination of the selling value of tax objects (NJOP) in five villages, namely the receipt of land and building tax obtained that the first PBB revenue is in the sulaa village with a total value of Rp. 952,394,544. The second is in the katobengke village with a total value of Rp. 556,270,502. Third, is the lipu village with a total value of Rp. 271,057,874. Furthermore, the waborobo village amounted to Rp. 45,077,786. and the labalawa village amounted to Rp. 39,575,965. Then the total accumulated PBB tax revenue of Betoambari Sub-district during 2015-2017 amounted to Rp. 1,864,376,671.